Overview Smoking Behavior and Quality of Life of Sports Department Students, Faculty of Sports Science, Universitas Negeri Malang - Rachmawati, Windi Chusniah; Ratih, Suci Puspita; Mawarni, Dian; Az Zahra, Aulia Rizqia; Ilmiyah, Chabibah; Putri, Fatiya Rizka; Kurnia, Nurmila; Jasmine Zhafirah Pribadi, Raden Roro; Novitasari, Zahra Rizki (Preventia: The Indonesian Journal of Public Health, 2024)
According to the results of the Global Adult Tobacco Survey (GATS) in 2021, there has been a considerable increase in the number of adult smokers over the past ten years, rising from 60.3 million in 2011 to 69.1 million in 2021, an increase of 8.8 million individuals. This study aims to compare the quality of life between actively smoking students and those who are exposed to passive smoking, examining their physical, psychological, social, and environmental health effects. The study utilized a sample of 100 respondents who completed a questionnaire on cigarette use and the WHOQOL quality of life assessment, covering variables such as cigarette type, disruption in daily activities, desire to quit smoking, cigarette consumption, and attitudes towards smoking bans in public places. Calculation of the WHOQOL score revealed that 60 percent of non-smoking student respondents reported a good quality of life. These findings underscore the critical need for enhanced health awareness programs and stricter smoking regulations within the university to foster a healthier environment. The study's insights highlight the importance of developing targeted interventions and policies to reduce smoking rates among students to enhance their overall quality of life.